Investigating African firms’ export performance: The role of marketing adaptation and institutional conditions - Mansouri, Samy; Kaswengi, Joseph; Hobeika, Janine (Management international / International Management / Gestiòn Internacional, 2024)
The literature on internationalization focuses on multinational companies, to the detriment of African companies. It is unclear how firms’ resources interact with environmental conditions in terms of marketing adaptation and export performance. Drawing on the resource-based view and the institutional perspective, this study uses survey data from 308 companies in Nigeria and Ghana. The results reveal that networking capacity, and the availability of financial resources positively influence marketing fit, which mediates the relationship between company resources and export performance. These effects depend on institutional conditions, with significant implications for the internationalization of African companies.